Predicting Job Satisfaction in Military Organizations: Unpacking the Relationship Between Emotional Intelligence, Teamwork Communication, and Job Attitudes in Spanish Military Cadets - Valor-Segura, Inmaculada; Navarro-Carrillo, Ginés; Extremera, Natalio; Lozano, Luis M.; García-Guiu, Carlos; Roldán-Bravo, María Isabel; Ruiz-Moreno, Antonia (Frontiers in Psychology, 2020)
Although prior research has extensively examined the association of emotional intelligence (EI) with various job attitudes (e.g., job satisfaction), empirical and systematic investigation of this link within military institutions has captured considerably less attention. The present research analyzed the relationship between EI, teamwork communication, and job satisfaction among Spanish military cadets. We tested the potential unique contribution of EI to job satisfaction over and above demographics (i.e., gender and age), proactive personality, and resilience. Moreover, we also examined whether EI was indirectly linked to job satisfaction via its relationship with teamwork communication. A sample of 363 cadet officers of the Spanish General Military Academy completed questionnaires assessing EI, teamwork communication, proactive personality, resilience, and job satisfaction. Hierarchical regression analysis revealed that EI exhibited incremental variance (ΔR2 = 5.2%) in predicting job satisfaction (B = .539, 95% CI [.306, .771]) even after accounting for demographics, proactive personality, and resilience. Additionally, mediation analysis showed that the association of EI with job satisfaction was partially driven by enhanced teamwork communication. This research provides empirical evidence suggesting a pathway (i.e., effective teamwork communication) through which EI could help military cadets to experience higher job satisfaction. Implications for future academic programs including EI and teamwork communication to promote positive job attitudes among military personnel are discussed.